Are We Moving Beyond Voluntary CSR? Exploring Theoretical and Managerial Implications of Mandatory CSR Resulting from the New Indian Companies Act - Gatti, Lucia (Journal of business ethics, 2019)
Although the literature on corporate social responsibility (CSR) has discussed the scope and meaning of CSR extensively, confusion still exists regarding how to define the concept. One controversial issue deals with the changing legal status of CSR (i.e., the voluntary vs. mandatory nature of the concept). Based on a review of CSR definitions and meta-studies on CSR definitions, we find that the majority of definitions leans toward voluntary CSR. However, some recent regulatory amendments toward mandatory CSR have called into question the established idea of CSR as merely a managerial tool of self-regulation. In this paper, we juxtapose the evolution of CSR in India against the scholarly literature discussing voluntary-versus-mandatory CSR to understand the recent shift toward a new conceptualization of CSR as a form of co-regulation that includes elements of both voluntary and mandatory regulation. The Indian Companies Act 2013 (Section 135) is a remarkable example in that it replaced an older version from 1956, taking a bold step toward the integration of voluntary and mandatory aspects in the application of CSR. We present practical implications of the Indian case for businesses and discuss implications for CSR theory development; we particularly consider the evolution of the business and society relationship from a voluntary soft law approach to CSR to an increasingly hard law approach and transitory hybrid forms in-between like soft–hard law and hard–soft law.